1993
DOI: 10.1093/nar/21.5.1245
|View full text |Cite
|
Sign up to set email alerts
|

HEX: a novel homeobox gene expressed during haematopoiesis and conserved between mouse and human

Abstract: We describe the cloning of a novel homeodomain-containing gene, which is highly conserved between mouse and human. The human cDNA was initially isolated from human haematopoietic tissue and denoted HEX (haematopoietically expressed homeobox). Sequence analysis of the coding sequences from mouse and the partial cDNA from human shows that the homeodomain is most closely related to those of the HIx and HOX11 proteins. The HEX gene is present as a single copy in the human genome. Analysis of murine genomic DNA sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 36 publications
2
112
0
4
Order By: Relevance
“…PRH functions in hematopoiesis (Bedford et al, 1993;Mani®oletti et al, 1995), in development of vascular endothelium and in its maintenance in adults (Newman et al, 1997;Thomas et al, 1998). PRH overexpression disrupts developing vascular structures and increases the number of vascular endothelial cells (Newman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRH functions in hematopoiesis (Bedford et al, 1993;Mani®oletti et al, 1995), in development of vascular endothelium and in its maintenance in adults (Newman et al, 1997;Thomas et al, 1998). PRH overexpression disrupts developing vascular structures and increases the number of vascular endothelial cells (Newman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PRH is a member of the orphan cluster of homeodomains (Crompton et al, 1992;Hromas et al, 1993;Bedford et al, 1993). It binds a known DNA binding sequence and the proline-rich region is not required for this activity (Crompton et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense riboprobes were synthesized using a DIG RNA labeling kit (Roche, #1 175 025) for the following genes: Bmp4 (Winnier et al, 1995), Cer1 (Belo et al, 1997), Fgf8 (Mahmood et al, 1995), Foxa2 ; Gbx2 (Wassarman et al, 1997), Hex (Bedford et al, 1993), Hesx1 (Thomas et al, 1995), Ebaf (previously Lefty2) (Meno et al, 1999), Lhx1 (Shawlot and Behringer, 1995), Lrp5 (Gong et al, 2001), Nodal (Meno et al, 1998), Pou5f1 (A. Smith), sprouty 2 (Minowada et al, 1999), Six3 (Oliver et al, 1995), Shh (Echelard et al, 1993), T (Wilkinson et al, 1990), Tbx6 (Image clone #599230) and Wnt3 (Roelink et al, 1990).…”
Section: Expression Analysis Of Whole-mount Embryosmentioning
confidence: 99%
“…We have also extended the transcriptional targets of Smad6 to include the Id2 gene, which had been previously shown to be induced during PMA-mediated HL-60 differentiation (Ishiguro et al, 1996) and the homeobox gene Hex, which had been shown to be involved in hematopoiesis (Bedford et al, 1993). Elements from each of these promoters were used in EMSAs and we observed a phenomenon similar to the OPN promoter; increased complex formation at these promoter elements that was enhanced by the inclusion of phosphorylated Smad6.…”
Section: Prkx Activity During Hl-60 Differentiation D Glesne and E Humentioning
confidence: 72%
“…To increase the putative repertoire of Smad6-responsive genes, we also screened the literature for genes whose expression is induced during hematopoiesis and regulated by TGF-b, bone morphogenetic protein (BMP) or Smads. We have identified two such candidate genes: the Id2 gene, which is induced during PMA-evoked macrophage differentiation (Ishiguro et al, 1996) and is responsive to TGF-b (Siegel et al, 2003) and BMP (Hollnagel et al, 1999), and the homeobox gene Hex, which has a potential role in hematopoiesis (Bedford et al, 1993) and is also regulated by BMP (Zhang et al, 2002). Within the promoter regions of the OPN, Id2 and Hex genes, there are putative Smad6-binding sequences.…”
Section: Prkx Activity During Hl-60 Differentiation D Glesne and E Humentioning
confidence: 99%